Implementasi Dana Ta’awun pada KSPPS Kota Padang Masa Pandemi Covid-19 - afriyanti afriyanti; Ulyadi Ulyadi (ITB AAS INDONESIA Surakarta, 2022)
Currently, the assets of Padang City KSPPS have reached Rp. 45,351,000,000 (June Balance Sheet Report KSPPS Padang City Government: 2020). The condition of the Covid-19 pandemic is a continuous problem, which has an impact on various sectors of life. The more concerning impact is on small communities who have micro businesses. Researchers are interested in studying more deeply how the principle of mutual assistance (ta'awun) is applied to the Padang City KSPPS during the Covid-19 pandemic. The implementation of the principle of mutual assistance can be seen in the management of ta'awun funds paid by participants on a regular basis. Ta'awun funds were collected with the aim of helping fellow participants who were stricken by disaster. The research is qualitative and field research. The method used is descriptive method. The implementation of ta'awun funds at the Padang City KSPPS during the covid-19 pandemic has not been implemented properly, because there are no rules or SOPs from the KSPPS Pemko itself in its implementation. However, the board and managers can make their own policies in implementing the ta'awun funds to be realized for members who experience disasters such as death, illness and others, both before the pandemic period and during the COVID-19 pandemic. The suitability of the implementation of the principle of ta'awun in Islam in the form of infaq does not contain an element of injustice, its designation is clear. The additional mandatory infaq in the financing contract is made separately in writing, so that there can be more clarity in the transaction between the two parties.